2013
DOI: 10.4187/respcare.02758
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Therapy for Severe Community-Acquired Pneumonia: A Meta-Analysis

Abstract: BACKGROUND:The debate about the efficacy of corticosteroids in the treatment of severe community-acquired pneumonia (CAP) is still a longstanding dilemma. We performed a meta-analysis including 4 randomized controlled trials (RCTs) to evaluate the effect of corticosteroids on the treatment of severe CAP in adults. METHODS: We performed a systematic review of published and unpublished clinical trials. Databases, including PubMed, Embase, CINAHL, and Cochrane (from their establishment to July 2013), were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 37 publications
(58 reference statements)
0
26
0
2
Order By: Relevance
“…There has been longstanding debate regarding the benefit of low-dose corticosteroid use in patients with CAP, but no consensus has been reached [4,[13][14][15][16][17][18][19][20]. Recent meta-analyses of randomised controlled trials found that even though low-dose corticosteroid use may not be beneficial to the overall population of patients with CAP, it may have a beneficial effect on mortality in patients with severe CAP and/or acute respiratory distress [13,[21][22][23]. However, recent small observational studies that focused on patients with severe CAP reported conflicting results [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…There has been longstanding debate regarding the benefit of low-dose corticosteroid use in patients with CAP, but no consensus has been reached [4,[13][14][15][16][17][18][19][20]. Recent meta-analyses of randomised controlled trials found that even though low-dose corticosteroid use may not be beneficial to the overall population of patients with CAP, it may have a beneficial effect on mortality in patients with severe CAP and/or acute respiratory distress [13,[21][22][23]. However, recent small observational studies that focused on patients with severe CAP reported conflicting results [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…В системном обзоре и метаанализе Ming Cheng et al [24] рассмотрена эффективность ГКС при тя желых формах приобретенной пневмонии, исходя из предпосылки, что тяжелая пневмония, которая яв ляется причиной острого повреждения легочной ткани, часто осложняется развитием респираторно го дистресс синдрома, а также сепсиса. Системная воспалительная реакция при пневмонии сопровож дается повышением активности провоспалительных цитокинов -интерлейкинов (IL) 6, 8, 10, 1β , TNF α, а также интерферона γ, экспрессия которых коррелирует со степенью тяжести течения пневмо нии.…”
Section: в исследовании Aemiller Et Alunclassified
“…The mortality benefit of corticosteroids remains uncertain, and if it does exist, it may be restricted to patients with severe CAP. 35,36 This suggests that the most compelling indication for corticosteroid use may be in patients with more severe CAP.…”
Section: 14mentioning
confidence: 99%
“…The Italian trial almost certainly overestimated the effect size: the mortality rate was higher than expected in the placebo group, and the trial was stopped early for benefit without predefined stopping criteria. 30 Meta-analyses prior to the most recent trials Meta--analyses of corticosteroids for CAP have reported varying findings, some suggesting a mortality benefit in those with severe CAP, 35,36 with low--dose corticosteroids, 37 or with prolonged administration. 35 No studies found a significant mortality benefit across all patients with CAP.…”
mentioning
confidence: 99%